Stabilization of organic municipal solid waste by composting - Tleuova Zh.О.; Мakeeva L.А.; Bayazitova Z.Е.; Kapbassova G.А.; Shaimerdenova Z.М. (Fundamental and Experimental Biology, 2022)
The article examines the process of vermicomposting of municipal organic waste. To determine the optimal composition of bio humus, various options and proportions of mixingorganic waste with soil are considered. In the course of the study, three different variations of organic waste were developed, mixed with manure: 1 — soil, paper, vegetables, fruits, wood waste, cow manure (1:0.5:1); 2 — soil, vegetables and fruits, wood waste (1:1); 3 — soil, cow manure (1:1). The results of the experiment showed that all substrates have high germination of tomato seeds. However, a mixture of soil, paper, vegetables,fruits, wood waste, cow manure increases the yield of tomatoes by 11 % compared to other experimental substrates. Vermicomposting E. was performed using E. fetida worms. This kind of worms is characterized by high yield. For vermic content, the moisture content must be at the level of 60 %. Bacteria also play an important role in vermicompost. With air humidity below 40 %, their activity decreases and stops at temperatures below 10 %.In this experiment, solid organic waste processing technology reduces the shortage of cheap organic fertilizers in the market and offers new opportunities for profit for small enterprises. The results obtained can be usedfor processing organic waste of the city on an industrial scale and applied as fertilizer in agriculture.